Quality of Life Outcomes in a Community Cohort of Adults With an Intellectual Disability Using the Personal Outcome Scale - Burke, Tom; Deffew, Andrew; Stafford, Owen; Docherty, Caroline; Burke, Sandra; Mostert, Remco; van Loon, Jos; Lombardi, Marco; Vaughan, Marianne; Brickell, Robert; Keogh, Mary; Mahon, Wendy; et al. (Frontiers in Rehabilitation Sciences, 2022)
Objectives: Quality of life (QoL) is a multi-dimensional phenomenon composed of core domains that are influenced by personal characteristics, values, and environmental contributions. There are eight core domains of quality of life aligned with both the United Nations and the International Association for the Scientific Study of Intellectual and Developmental Disabilities (IASSIDD). The Personal Outcome Scale (POS), is a semi-structured self and proxy instrument which specifically measures these aspects of QoL for people with an intellectual disability. Methods: 85 people with an intellectual disability and their primary keyworker (n=85) took part in this study. A convenience sample recruitment strategy was employed to recruit participants during the calendar year from January-December 2020. Participants completed the self-report and proxy POS, and clinic-demographic data was also considered. Results: QoL is higher in those who have a dedicated service planner, and was higher for those with a less severe to profound disability. People who were in gainful employment reported significantly higher QoL, as did those availing of Outreach and Residential services, over and above Local services. Conclusions: This research shows that there are distinct and specific factors which relate to QoL for people with an intellectual disability community-based services in Ireland. Future research could aim to investigate these longitudinally, and specifically how QoL relates to cognitive and functional outcomes.